Interhemispheric Asymmetries in the Ground Magnetic Response to Interplanetary Shocks: The Role of Shock Impact Angle. Issue 3 (13th March 2020) - Xu, Z.; Hartinger, M. D.; Oliveira, D. M.; Coyle, S.; Clauer, C. R.; Weimer, D.; Edwards, T. R.
Abstract: Interplanetary (IP) shocks drive magnetosphere‐ionosphere (MI) current systems that in turn are associated with ground magnetic perturbations. Recent work has shown that IP shock impact angle plays a significant role in controlling the subsequent geomagnetic activity and magnetic perturbations; for example, highly inclined shocks drive asymmetric MI responses due to interhemispherical asymmetric magnetospheric compressions, while almost head‐on shocks drive more symmetric MI responses. However, there are few observations confirming that inclined shocks drive such asymmetries in the high‐latitude ground magnetic response. We use data from a chain of Antarctic magnetometers, combined with magnetically conjugate stations on the west coast of Greenland, to test these model predictions (Oliveira & Raeder, 2015, https://doi.org/10.1002/2015JA021147 ; Oliveira, 2017, https://doi.org/10.1007/s13538-016-0472-x ). We calculate the time derivative of the magnetic field ( ∂ B / ∂ t ) in each hemisphere separately. Next, we examine the ratio of Northern to Southern Hemisphere ∂ B / ∂ t intensities and the time differences between the maximum ∂ B / ∂ t immediately following the impact of IP shocks. We order these results according to shock impact angles obtained from a recently published database with over 500 events and discuss how shock impact angles affect north‐south hemisphere asymmetries in the ground magnetic response. We find that the hemisphere the shock strikes first usually has (1) the first response in ∂ B / ∂ t and (2) the most intense response in ∂ B / ∂ t . Additionally, we show that highly inclined shocks can generate high‐latitude ground magnetic responses that differ significantly from predictions based on models that assume symmetric driving conditions. Key Points: High latitude interhemispheric comparisons are performed to study asymmetries in ground magnetic perturbations caused by shock inclinations The hemisphere the shock strikes first usually has (1) the first response in ∂ B / ∂ t and (2) the most intense response in ∂ B / ∂ t Impact angles are an important parameter controlling the timing and intensity of the ground magnetic response to interplanetary shocks